Dampak Tingkat Suku Bunga Dan Inflasi Terhadap Harga Saham Melalui Keputusan Investasi Sebagai Variabel Moderasi Pada Perusahaan Sektor Properti Di Bei Periode 2020-2024 - Jesica Neldi Utami; Elfiswandi .; Rindy Citra Dewi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to examine the effect of interest rates and inflation on stock prices, with investment decisions serving as a moderating variable. The independent variables in this study are interest rates and inflation, while the dependent variable is stock prices, and the moderation variable is investment decisions. The research method used is Moderated Regression Analysis (MRA) using EViews 10 software. The results of this study indicate that interest rates have a positive and significant effect on stock prices. Inflation has a positive but insignificant effect on stock prices. The moderating effect of investment decisions on the relationship between interest rates and stock prices is positive and significant. Meanwhile, the moderating effect of investment decisions on the relationship between inflation and stock prices is positive but insignificant. This study has implications for investors in making investment decisions in the Indonesian capital market, particularly the stock market.